Spontaneous coronary artery dissection in a patient with hereditary polycystic kidney disease and a recent liver transplant: a case report. Issue 4 (13th December 2019) - Verlaeckt, Ezther; Van de Bruaene, Laurens; Coeman, Mathieu; Gevaert, Sofie
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is an underestimated cause of acute coronary syndromes. A predisposing arteriopathy is often present and a stressor can sometimes be identified. Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disorder; its associated arteriopathy has been described as a predisposing condition for SCAD. Case summary: A 44-year-old woman with ADPKD presented in the emergency room with recent onset thoracic pain radiating to the left arm at rest. She had undergone a recent liver transplant, for which she had received high-dose corticosteroids during 1 month. She was still taking tacrolimus and mycophenolate mofetil. She had no traditional risk factors but had experienced stress postoperatively. She was known with moderate chronic kidney disease. The initial electrocardiogram (ECG) was normal but high-sensitive troponin T was significantly elevated. Coronary angiography demonstrated diffuse narrowing of the distal left anterior descending artery with preserved flow, compatible with a SCAD Type 2 that was treated conservatively. However, under dual antiplatelet therapy (DAPT) with clopidogrel, the coronary dissection was progressive with new ischaemic ECG changes, further rise of troponins and development of apicoseptal hypokinesia. Because of the small vessel diameter and the preserved distal flow, conservative treatment was maintained. Clopidogrel was interrupted and the patient remained stable. Discussion: As SCAD remains an underestimated cause of myocardial infarction, clinicians should be aware of the possibility of SCAD in ADPKD patients with chest pain. This case report illustrates that the decision DAPT vs. aspirin should be individualized in these patients.